1994
DOI: 10.1016/s0022-5347(17)35351-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Allopurinol Pretreatment Before Detorting Testicular Torsion

Abstract: The resumption of blood flow to organs following ischemia may cause a further increase in tissue damage through an increase in peroxidation of lipids in cell membranes. An experimental study was conducted to investigate the prevention of reperfusion injury after testicular torsion through changes in the lipid peroxide content of the testis. Adult male albino rats were divided into 11 groups, each containing 10 rats. One group served to determine base values of the lipid peroxide content of the testis and kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 6 publications
4
49
0
3
Order By: Relevance
“…Akgür, Lysiak, Bozlu, Abasıyanık and Ozkan et al showed that allopurinol, catalase and catalase plus superoxide dismutase and poly (ADP-ribose) polymerase inhibitors, melatonin and zinc aspartate treatments decreased the lipid peroxidation product (MDA). 9,15,18,19,37 We found that MDA level was significantly decreased by trapidil in testicular torsion and detorsion in our study also.…”
Section: Discussionsupporting
confidence: 71%
“…Akgür, Lysiak, Bozlu, Abasıyanık and Ozkan et al showed that allopurinol, catalase and catalase plus superoxide dismutase and poly (ADP-ribose) polymerase inhibitors, melatonin and zinc aspartate treatments decreased the lipid peroxidation product (MDA). 9,15,18,19,37 We found that MDA level was significantly decreased by trapidil in testicular torsion and detorsion in our study also.…”
Section: Discussionsupporting
confidence: 71%
“…9 The significant increase of MDA levels at the end of the ischemia and during the reperfusion in rats submitted to the torsion of the spermatic cord show that 3-h ischemia promotes severe cell membrane peroxidation (Figure 1). On the other hand, the additional increase of MDA levels 1h and 3 h after detorsion of the spermatic cord reassures that additional injuries occur during reperfusion as has been reported previously by Akgur et al 10 Glutathione (GSH) is a tripeptide, L-g-glutamyl-L-cysteinyl-glycine, mol. wt.…”
Section: Discussionsupporting
confidence: 68%
“…10 experiment elicited a significant increase in TBARS in torted testis (p<0.01) and further increase was caused by detorsion (reperfusion). Pretreatment with allopurinol before detorsion prevented reperfusion injury.…”
Section: Discussionmentioning
confidence: 95%
“…Different therapeutic strategies have been investigated with the aim of reducing testis ischemia/reperfusion damage [10][11][12][13] . The aim of the present study was to evaluate, in an experimental model of testis I/R the effects of DMSO on tissue and plasma oxidative stress in twisted testis after unilateral torsion and detorsion.…”
Section: Introductionmentioning
confidence: 99%